Exposure to PFDoA causes disruption of the hypothalamus-pituitary-thyroid axis in zebrafish larvae. (April 2018) - Zhang, Shengnan; Guo, Xiaochun; Lu, Shaoyong; Sang, Nan; Li, Guangyu; Xie, Ping; Liu, Chunsheng; Zhang, Liguo; Xing, Yi
Abstract: Perfluorododecanoic acid (PFDoA), a kind of perfluorinated carboxylic acid (PFCA) with 12 carbon atoms, has an extensive industrial utilization and is widespread in both wildlife and the water environment, and was reported to have the potential to cause a disruption in the thyroid hormone system homeostasis. In this study, zebrafish embryos/larvae were exposed to different concentrations of PFDoA (0, 0.24, 1.2, 6 mg/L) for 96 h post-fertilization (hpf). PFDoA exposure caused obvious growth restriction connected with the reduced thyroid hormones (THs) contents in zebrafish larvae, strengthening the interference effect on the growth of fish larvae. The transcriptional level of genes within the hypothalamic-pituitary-thyroid (HPT) axis was analyzed. The gene expression levels of thyrotropin-releasing hormone ( trh ) and corticotrophin-releasing hormone ( crh ) were upregulated upon exposure to 6 mg/L of PFDoA, and iodothyronine deiodinases ( dio2 ) was upregulated in the 1.2 mg/L PFDoA group. The transcription of thyroglobulin ( tg ) and thyroid receptor ( trβ ) were significantly downregulated upon exposure to 1.2 mg/L and 6 mg/L of PFDoA. PFDoA could also decrease the levels of sodium/iodide symporter ( nis ) and transthyretin ( ttr ) gene expression in a concentration-dependent manner after exposure. A significant decrease in thyroid-stimulating hormoneβ ( tshβ ), uridinediphosphate-glucuronosyltransferase ( ugt1ab ) and thyroid receptor ( trα ) gene expression were observed at 6 mg/L PFDoA exposure. Upregulation and downregulation of iodothyronine deiodinases ( dio1 ) gene expression were observed upon the treatment of 1.2 mg/L and 6 mg/L PFDoA, respectively. All the data demonstrated that gene expression in the HPT axis altered after different PFDoA treatment and the potential mechanisms of the disruption of thyroid status could occur at several steps in the process of synthesis, regulation, and action of thyroid hormones. Graphical abstract: Image 1 Highlights: Zebrafish embryos were exposed to different concentrations of PFDoA for 96 hpf. PFDoA exposure resulted in decrease of TSHβ contents in zebrafish larvae. Alterations of THs levels indicated thyroid endocrine disruption induced by PFDoA. Genes involved in HPT axis were also modulated after PFDoA exposure. Abstract : Exposure to PFDoA could alter thyroid hormone levels as well as gene transcription involved in the hypothalamus-pituitary-thyroid axis in zebrafish larvae, causing endocrine disruption of the thyroid system.